Chemical composition of the Kaempferia galanga L. essential oil and its in vitro and in vivo antioxidant activities - Wang, Si-Yu; Cai, Lei; Yang, Na; Xu, Fang-Fang; Wu, Yun-Shan; Liu, Bo (Frontiers in Nutrition, 2023)
Kaempferia galanga L. is an important medicine rich in high value essential oil. K. galanga essential oil (KGEO) has been used in folk medicine for treating indigestion, skin issues, rheumatism, and asthma. In this study, the composition of KGEO was identified, and the major components were ethyl trans-p-methoxycinnamate (32.01%), n-pentadecane (29.14%) and trans-ethyl cinnamate (19.50%). Pharmacological results in vitro showed that KGEO processing good free radicals scavenging capacity in DPPH, ABTS, hydroxyl radicals scavenging assays (IC50 values: 19.77±1.28, 1.41±0.01, 3.09±0.34 mg/mL) and weak reducing capacity in reducing power assay (EC50 value: 389.38±4.07 mg/mL). Furthermore, zebrafish model was adopted to evaluate the protective effect of KGEO on H2O2-induced oxidative stress damage. After KGEO treatment, the survival rate and heart rate increased, ROS generation, cell death, and lipid peroxidation were attenuated. In addition, decrease of MDA levels and increase SOD, CAT and GSH-Px activities were observed in KGEO treated groups. This study validated the in vitro and in vivo antioxidant activities of KGEO, which provides a theoretical basis for a profound study of KGEO, and its application in pharmaceutical, food and cosmetic industries.